PHYTOCHEMICAL AND CYTOTOXICITY TESTING OF RAMANIA LEAVES (Bouea macrophylla Griffith) ETHANOL EXTRACT TOWARD VERO CELLS USING MTT ASSAY METHOD (Preliminary study of adjuvant therapy materials to the preparation of the drug) - Laila Fitri; Irham Taufiqurrahman; Irnamanda DH (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Ramania leaves (Bouea macrophylla Griffith) are one of the local medicinal plants of South Kalimantan which is used as adjuvant therapy material. Previous research showed that ramania leaves ethanol extract showed that the extract has potential as adjuvant therapy material for anticancer, but the safety of this material is not yet known so it  needs to be tested with cytotoxicity test to know the toxic properties of the material toward normal cells in vitro. Objective: This research aims to determine the cytotoxicity properties of ramania leaves ethanol extract toward Vero cells using MTT assay method. Method: It was a true experimental research using posttest-only with control group design consist of 8 treatment groups: 31.25μg/mL, 62.5μg/mL, 125μg/mL, 250μg/mL, 500μg/mL, 1000μg/mL, 2000μg/mL and 4000μg/mL and 2 control groups which were cell control and media control. Study phases include phytochemical test, tannic acid test, cell culture, harvest and cell calculation and cytotoxicity test. The result test was read by ELISA reader, the absorbance will be calculated  by a  formula. Results: The test result showed that ramania leaves ethanol extract contained secondary metabolite such as phenol, flavonoid, steroid and terpenoid. The identification test of tannic acid compound  using TLC method (thin layer chromatography) showed the presence of tannic acid compound.The probit analysis showed IC50in 35.808μg/mL. Conclusion: Based on the research, it can be concluded that ramania leaves ethanol extract are found cytotoxic toward Vero cells after the analysis using MTT assay method (IC50<100μg/mL).